2004
DOI: 10.1248/cpb.52.41
|View full text |Cite
|
Sign up to set email alerts
|

HPLC Retention Behavior of Poly-Aromatic-Hydrocarbons on Aminopropyl Silica Gels Modified with Cu(II)- and Ni(II)-Phthalocyanine Derivatives in Non-polar Eluent

Abstract: were purchased from Aldrich, U.S.A. Phthalocyanine (H 2 -PC) was obtained from Tokyo Kasei, Japan. As a supports, Develosil NH 2 -5 ® (hereinafter, referred to as "Dev", Nomura Kagaku, Japan) which is a spherical aminopropyl silica gels (particle size, 5 mm; specific surface area, 350 m 2 /g; average pore size, 120 Å) was used. As an eluent, n-hexane for HPLC (Nacalai Tesque, Japan) was mainly used, and as a solvent for packing M-PCS D , slurry solvent A Conc. (Chemco Scientific, Japan) was used. The commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…As we previously reported, 12 anthrathene derivatives having a substituent(s) show similar k values, and cannot be separated in a non-polar eluent. We therefore investigated the retention behavior of anthrathene derivatives on Cu-PCSD and Ni-PCSD in a polar eluent, i.e., 80% or 90% methanol.…”
supporting
confidence: 61%
See 3 more Smart Citations
“…As we previously reported, 12 anthrathene derivatives having a substituent(s) show similar k values, and cannot be separated in a non-polar eluent. We therefore investigated the retention behavior of anthrathene derivatives on Cu-PCSD and Ni-PCSD in a polar eluent, i.e., 80% or 90% methanol.…”
supporting
confidence: 61%
“…4. Considering that the k values on the Cu-PCSD column showed a linear correlation with those on the PYE column lacking a central metal in n-hexane, 12 the above results indicated that the π-π electron interaction is dominant in 80% methanol.…”
mentioning
confidence: 72%
See 2 more Smart Citations